Randomised immunogenicity trial comparing 2019-2020 recombinant and egg-based influenza vaccines among frequently vaccinated healthcare personnel in Israel - Ashley L. Fowlkes; Alon Peretz; David Greenberg; Avital Hirsch; Emily T. Martin; Min Z. Levine; Laura Edwards; Sarah Radke; Adam S. Lauring; Jill M. Ferdinands; Chao Zhang; Young M. Yoo; et al. (International Journal of Infectious Diseases)
Objectives: Trivalent inactivated influenza vaccine effectiveness was low in a prospective cohort of healthcare personnel (HCP) in Israel from 2016 to 2019. We conducted a randomised immunogenicity trial of quadrivalent recombinant influenza vaccine (RIV4) and standard-dose inactivated influenza vaccine (IIV4) among frequently and infrequently vaccinated previous cohort participants. Methods: From October 2019 to January 2020, we enrolled and randomly allocated HCP from two Israeli hospitals to receive IIV4 or RIV4. Hemagglutination inhibition (HAI) antibody titres against 2019-2020 vaccine reference influenza viruses were compared between vaccine groups using geometric mean titre (GMT) ratios from sera collected one-month post-vaccination and by frequency of vaccination in the past 5 years (>2 vs ≤2). Results: Among 415 HCP, the GMT ratio comparing RIV4 to IIV4 was 2.0 (95% confidence interval [CI] 1.7-2.7) for A(H1N1)pdm09, 1.6 (95% CI: 1.3-1.9) for A(H3N2), 1.8 (95% CI: 1.4-2.2) for B(Yamagata), and 1.1 (95% CI: 0.9-1.4) for B(Victoria). Similarly, RIV4 elicited higher HAI titres than IIV4 against all 2019-2020 vaccine reference viruses except B(Victoria) among infrequently and frequently vaccinated HCP (lower bound of GMT ratio 95% CIs ≥1.0). Conclusion: RIV4 had improved immunogenicity for influenza vaccine strains among both infrequent and frequent vaccinees compared to standard-dose IIV4. Clinical trials registration: NCT04523324